Trading the silver seed : local knowledge and market moralities in aquacultural development - Lewis, David J.; Wood, Geoffrey D., 1945-; Gregory, Rick. (Dhaka, Bangladesh : University Press, 1996)
Study on social, economic and technical aspects of aquaculture in Bangladesh.
Includes bibliographical references (p. [189]-194) and index.
Keywords: Aquaculture industry -- Bangladesh; Economic development projects -- Bangladesh; Aquaculture -- Bangladesh